Effect of direct-fed microbial addition in guinea fowl (Numida meleagris) diets on performance and health responses - Sarfo, G.K.; Larbi, Asamoah; Hamidu, J.A.; Donkoh, A. (Elsevier, 2018)
The present study was conducted to investigate the effect of intermittent use of direct-fed microbial addition (DFM-“RE3®”) on growth performance and health status of indigenous guinea fowls in northern Ghana. One-hundred and eighty day-old guinea keets were randomly assigned to 4 direct-fed microbial (DFM) treatments that included: control, daily, 3 consecutive days per wk (3CDW), and 7 days repeated every other wk (7DREOW) at 1.5 ml/L through water from day 1 to 56 days. Feed intake, body weight gain, and blood hematological and serum biochemical properties were recorded. The treatments had no effects (P > 0.05) on the hematological or serum biochemical properties recorded. Birds on DFM treatments appeared to consume less feed (range: 1,584 to 1,824 g/d) compared to the control (1,870 g/d/head). Birds on DFM treatments daily and 3CDW gained more (P < 0.05) weight (334 to 394 g/d) compared to the control (306.1 g/head) with keets on daily DFM supplementation recording the lowest (P < 0.05) feed conversion ratio. The total blood protein, globulin, lipids, albumin concentrations, and cholesterol concentrations were not affected (P > 0.05) by DFM supplementation. Supplementing birds with 1.5 mL of RE3®/liter of water daily can improve body weight. Further research on immune competence from the spleen, thymus, and bursa fibrosis for evidence of increased immune competence in probiotic administered birds is recommended.